2023
DOI: 10.1039/d2va00236a
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of carbon capture, utilization and storage for mitigating climate change

Abstract: Carbon capture storage (CCS) and carbon capture utilization (CCU) are recognized as potential pathways to combat global climate change. Numerous efforts are underway, such as CCS (e.g., biochar used for...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 122 publications
0
20
0
Order By: Relevance
“…8 It is noteworthy that the adoption of numerous transition paths may be necessary to achieve a carbon-neutral economy, given the apparent inadequacy of a single road. 9 Recently, Zuraiqi et al revealed an advanced CCS technology where produced CO 2 is permanently locked into solid-state carbon using Ga-In liquid metal alloy catalyst at low temperature. 10 However, further research at the fundamental level is needed to support this new born technology.…”
Section: Introductionmentioning
confidence: 99%
“…8 It is noteworthy that the adoption of numerous transition paths may be necessary to achieve a carbon-neutral economy, given the apparent inadequacy of a single road. 9 Recently, Zuraiqi et al revealed an advanced CCS technology where produced CO 2 is permanently locked into solid-state carbon using Ga-In liquid metal alloy catalyst at low temperature. 10 However, further research at the fundamental level is needed to support this new born technology.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Even a slight change in the orbital structure or microscopic structural forms of carbon can result in an extensive range of captivating properties in terms of minimal selling price and environmental impacts of biochar were studied through TEA and cradle-to-grave LCA. 32,33 The economic feasibility of biochar production was investigated using forest residues as feedstock in a small-scale portable machine. Based on their studies, the minimum selling price of biochar can be below $1000 per ton.…”
Section: Introductionmentioning
confidence: 99%
“…The global concern over climate change and the urgent need to mitigate greenhouse gas emissions have highlighted the importance of carbon capture and utilization (CCU) technologies. CCU not only helps in reducing emissions of CO 2 (i.e., the major greenhouse gas) but also presents opportunities for the production of valuable chemicals and fuels simultaneously. ,, As such, the development of efficient CCU processes is critical in addressing the challenges of climate change and transitioning to a more sustainable future in chemical engineering. , …”
Section: Introductionmentioning
confidence: 99%
“…2,3,5 As such, the development of efficient CCU processes is critical in addressing the challenges of climate change and transitioning to a more sustainable future in chemical engineering. 6,7 Among the various CCU technologies, calcium looping (CaL) has emerged as one of the most prominent techniques. Calcium looping utilizes the reversible reaction between calcium oxide (CaO) and CO 2 , enabling the cyclic capture and release of CO 2 8−13 + CaO(s) CO (g) CaCO (s)…”
Section: ■ Introductionmentioning
confidence: 99%